The Influence of Human Resource Development on the Professionalism and Integrity of Police Members: JEL Classification: M12, M53, J24, J45. K42 - Muin, Sri Adrianti; Halik, Johan; Malik, Abd; Bahi, Musriaddin (Newinera Publisher, 2025)
This paper examines the impact of human resource development (HRD) strategies on the professionalism and integrity of the police officers in Police Station Takalar, South Sulawesi in Indonesia. It also analyses four HRD dimensions based on the quantitative explanatory approach using training and education, ethical guidance, career management, and recruitment systems. Proportional stratified random sampling of 125 respondents using structured questionnaires was used to collect the data to ascertain the impact of each of the HRD components. The results indicate that training and education are the most influential ones, then ethical guidance and career management are moderate ones and recruitment is lower but not negligible. These findings point to the vitality of continuing professional growth and training centered on ethics in reinforcing both competence and moral uprightness in police officers. Another area of research that is covered is the absence of empirical research on how integrated HRD policies influence institutions that are in charge of national security. This study is unique in the sense that in contrast to earlier researches where the primary methods used were qualitative or normative, this study presents quantitative evidence that can be used to make more effective and responsible HRD policies. Implications include that the police institution reforms must focus on systemic capacity building as a strategic investment to increase credibility and community trust of the law enforcers.